SEMANTIC CHARACTERISTICS OF NOUNS IN THE ENGLISH LANGUAGE - Elmurodova Nozima Sherzod kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. Nouns represent one of the core lexical categories in the English language and play a central role in meaning construction and reference. This article examines the semantic characteristics of English nouns, focusing on their conceptual, functional, and classificatory features. Special attention is given to semantic distinctions such as concreteness and abstractness, countability, animacy, proper and common reference, and semantic extension through metaphor and metonymy. The study also considers the role of nouns in lexical relations and discourse organization.